2022
DOI: 10.3390/nano12101659
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Humidity Sensor with GO-Mn-Doped ZnO Nanocomposite and Dimensional Orchestration of Comb Electrode for Effective Bulk Manufacturing

Abstract: The measurement and control of humidity is a major challenge that affects the sensing properties of sensors used in high-precision equipment manufacturing industries. Graphene Oxide(GO)-based materials have been extensively explored in humidity sensing applications because of their high surface area and functional groups. However, there is a lack of effective bulk-manufacturing processes for the synthesis of 2D-based nanocomposites with comb electrodes. Moreover, water intercalation within the layers of 2D mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The RH in the humidity test chamber was provided by atomized water (wet air) produced by a desktop humidifier. The processes of introducing the produced wet air into the humidity test chamber, controlling the RH percentage, and removing the wet air from the chamber were carried out with a computer-controlled Arduino-based automatic feedback controller [50]. In this way, possible fluctuations/variations of the humidifier used were minimized and measurements were made in a more controlled manner.…”
Section: Electrical Conductivity and Humidity Sensing Measurementsmentioning
confidence: 99%
“…The RH in the humidity test chamber was provided by atomized water (wet air) produced by a desktop humidifier. The processes of introducing the produced wet air into the humidity test chamber, controlling the RH percentage, and removing the wet air from the chamber were carried out with a computer-controlled Arduino-based automatic feedback controller [50]. In this way, possible fluctuations/variations of the humidifier used were minimized and measurements were made in a more controlled manner.…”
Section: Electrical Conductivity and Humidity Sensing Measurementsmentioning
confidence: 99%
“…For example, at 40% relative humidity (RH), the response time of GO nanocomposite is 82.67 times that of normal conditions, and its sensitivity is 95.7 times that of normal conditions at 60%RH. 125 Wang et al. found that the GO humidity sensor has a frequency change of 103 kHz/%RH at low humidity (30–60%RH).…”
Section: Applications Of Biomedical Applicationsmentioning
confidence: 99%
“…These properties make GO potentially useful as a sensing material. Further, GO is more compatible with polymers than pure graphene, and it is a good candidate for chemical sensing applications [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%